Media and campaign effects on vote choice at national elections in Europe: a review of a multilingual research landscape - Boomgaarden, H. (2017)
This article reviews the empirical research literature on campaign and media effects on vote choice at national elections in European countries for the post-World War II period. Particular efforts are undertaken to obtain a comprehensive picture by including publications in many different languages. With regard to the amount of research, but also the topics addressed, the survey reveals considerable differences between countries. Studies of campaign effects have focused on the temporal dynamics of campaigns, on the modes of campaign communications (such as personal contacts at the local level, advertising on TV and in the press or online social media) and on certain aspects of its content. Research on media effects has explored the role of partisan bias and certain topical categories of news (climate of opinion, issue and candidate coverage) as well as specific new media formats, notably televised candidate debates and vote advice applications (VAA). Overall, the review reveals that there is little in the way of an integrated and consolidated body of campaign and media effects research on national elections in Europe. While political communication research increasingly acknowledges the potential importance of news media and political parties’ electioneering for voting behaviour, there appears as of yet to be little convergence regarding approaches and research findings. Particularly striking is the degree to which research questions are guided by national institutional contexts.